Meningkatkan Hasil Belajar Pakat dan Mandiri Melalui Model Discovery Learning Fase F SMA Negeri 1 Siantar Narumonda - Umiar Simarsoit (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The aim of this Classroom Action Research is to find out and measure whether or not the students of class The research subjects were 13 class XI students of SMA N 1 Siantar Narumonda, consisting of 5 men and 8 women. The object of the research is the learning outcomes and student independence in learning Catholic Religion and Ethics in teaching module 1 "The Church as God's people" and improvements in teaching module 2 "Church and the world". With data collection techniques, namely observation, documentation and tests. The results of the research show that there is an increase in learning outcomes and independence for Class The increase in learning outcomes and independence is proven by the average score for increasing independence in cycle I of 60.5% and in cycle II it increased by 25%, namely 85.5%. And the increase in learning outcomes in cycle 1 was 67% and in cycle II it increased by 27%, namely 94%.